(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
One way to overcome the problems of ‘proxy’ women is,according to Dahlerup and Freidenvall, massive capacity-building and supportfrom women’s organizations . The capacity building trainings aim to educatewomen about their rights and help them to become more equal. The basic approachwould be to give women confidence and bring out an awareness of their ownpotential for development as well as their rights and privileges. Already in1985 at the World Conference of the UN in Nairobi it was stated that NGOs andthe governmental education of women about their civil, political and socialrights is one of the most important ways of rising consciousness, but also theneed for a quota system . Education is a powerful tool in the way of empoweringwomen . During my time in the field I could see that education enables women togain more knowledge about the world outside of their heart and home, increasetheir skills and help them to get status-giving employment – all of which willdevelop their personalities.